Microanalysis of E-Money Transfer Services through E-Servqual Approach: A Basis for Enhanced Customer Satisfaction Strategy - Santillan, Cyrene Joy P.; Mendoza, Xavier Lawrence D.; Tadeo, Jerico B. (Garuda Prestasi Nusantara Consulting, 2023)
Adopting various technologies in enterprises was vital since it provided a quick service process. E-money transfer services study aimed to evaluate customer satisfaction with e-money transfer services using E-SERVQUAL Approach. The researchers used a descriptive-correlational research design and purposive sampling to select 100 e-money transfer service customers in selected Cavite municipalities. The study's results revealed that the participants were primarily young adult females, commonly single. The results showed that most participants were college undergraduates with a monthly income of Php 10,000 and below. The study showed that the customers were highly satisfied with e-money transfer services regarding reliability, security, website design, accessibility, and personalization. In contrast, in terms of responsiveness, the customers were satisfied. The study found that the biggest challenges in utilizing e-money transfer services were lack of prompt responses, slow money processing, the possibility of committing fraud, lack of creativity of the website, not an accessible website, and lack of expertise. This study showcased that the age of customers has a significant difference to the reliability of e-money transfer services. This study recommended that e-money transfer services improve the e-service quality for customer satisfaction. Keywords: E-money transfer services, customer satisfaction, online services, E-SERVQUAL